De Galerie. - Stichting De Galerie, Leeuwarden (Dokkum : Uitgeverij Kalamiteit, 1987)
Spinder, Catrinus ; Tanis, Astrid ; De Vos, Paul ; Du Puy, Armand ; Selie, Hans ; Gerbenzon, Nico ; Egberts, Otto ; Verkerk, Hans ; Jolink, René ; Willemsma, Ids ; etc.
jaaroverzicht van de tentoonstellingen
boek